A li+/Na+ hybrid rechargeable full battery comprising rice husk porous hard carbon anode and sodium vanadium phosphate - Xiangxiang Chen; Xingchen Pan; Yixin Zhao; Zhiyong Xie (Electrochemistry Communications)
As the demand for affordable and safe energy storage options surges, the quest for hybrid ion batteries that effectively combine the strengths of Lithium-Ion Batteries (LIBs) and Sodium-Ion Batteries (SIBs) is gaining momentum. This study introduces an innovative hybrid lithium/sodium ion full battery (HIB), which features a porous hard carbon (PHC) anode and a high-energy sodium-based cathode, Na3V2(PO4)3 (NVP). Upon assembly, these HIBs demonstrate a commendable operating voltage of approximately 3.5 V, alongside a discharge-specific capacity of 92.9 mAh/g. Furthermore, they reveal impressive capabilities in terms of high-rate performance, cycling stability, and reversible capacity. The investigation into the reaction kinetics and the mechanisms behind lithium/sodium insertion and extraction in this hybrid battery was initially conducted through ex-situ XRD and ex-situ XPS analyses. This research opens up new avenues and perspectives for further advancements in hybrid ion battery technology.